1989
DOI: 10.1128/mcb.9.7.3105-3108.1989
|View full text |Cite
|
Sign up to set email alerts
|

Each of the Conserved Sequence Elements Flanking the Cleavage Site of Mammalian Histone Pre-mRNAs Has a Distinct Role in the 3′-End Processing Reaction

Abstract: To study the substrate requirements for the histone 3'-end processing reaction of mammalian histone pre-mRNAs, we created a set of mutations in the sequences flanking the processing site of a mouse H3 gene. We found that deletion of the downstream purine-rich element hypothesized to interact with U7 small nuclear RNA abolishes in vitro 3'-end processing. Somewhat surprisingly, however, mutations in the hairpin loop element which destabilize or destroy the secondary structure reduce but do not abolish 3'-end pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The nuclear SLBP is detected efficiently by the mobility-shift assay , suggesting that it is not bound to histone mRNA. The stem-loop at the 3′ end of histone mRNA is also important in processing of the 3′ end of histone mRNA, and there is a hairpin-binding factor involved in the 3′ end formation that recognizes the stem-loop (Melin et al, 1992;Vasserot et al, 1989;Mowry et al, 1989;Mowry & Steitz, 1987). Recently, we have shown that the polyribosomal SLBP can complement a nuclear processing extract deficient in the hairpin-binding factor (Dominski et al, 1995), suggesting that the SLBP is the hairpin-binding factor (or part of the hairpin-binding factor) required for histone 3′ end formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nuclear SLBP is detected efficiently by the mobility-shift assay , suggesting that it is not bound to histone mRNA. The stem-loop at the 3′ end of histone mRNA is also important in processing of the 3′ end of histone mRNA, and there is a hairpin-binding factor involved in the 3′ end formation that recognizes the stem-loop (Melin et al, 1992;Vasserot et al, 1989;Mowry et al, 1989;Mowry & Steitz, 1987). Recently, we have shown that the polyribosomal SLBP can complement a nuclear processing extract deficient in the hairpin-binding factor (Dominski et al, 1995), suggesting that the SLBP is the hairpin-binding factor (or part of the hairpin-binding factor) required for histone 3′ end formation.…”
Section: Discussionmentioning
confidence: 99%
“…The polyA sequence present at the 3′ end of most mRNAs has a number of functions in mRNA metabolism, which are mediated by interaction with the polyA binding protein (Sachs et al, 1987;Sachs & Davis, 1989;Bernstein & Ross, 1989;Jackson & Standart, 1990), including participating in translation (Gallie, 1991;McGrew & Richter, 1990;Munroe & Jacobson, 1990) and contributing to mRNA stability. Similarly, the 3′ end of histone mRNA is involved in mRNA processing (Melin et al, 1992;Vasserot et al, 1989;Mowry et al, 1989), transport (Williams et al, 1994), translation (Sun et al, 1992) and regulation of stability (Sun et al, 1992;Marzluff, 1992). These functions are likely mediated by interaction with specific protein(s).…”
mentioning
confidence: 99%
“…Since this finding was not compatible with previous reports of replication-dependent histone mRNAs in higher vertebrates, we isolated the corresponding genomic clone. The genomic sequence contained both the classical hairpin loop structure and the conserved downstream purine-rich element, which interacted with U7 nuclear RNA in the 3'-end processing of the nonpolyadenylated histone pre-mRNAs (38). Immediately upstream from the hairpin loop the genomic clone contained an oligo[d (A4GA10)] sequence on the DNA strand corresponding to the mRNA sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in which altered sequences of several histone genes have been used have been performed to elucidate the molecular mechanisms and the sequence motifs essential for cell-cycle-dependent regulation of the replication-dependent histone mRNAs (1,22,30,33,38). The abundantly expressed histone H2A.1 gene characterized in this paper might also be valuable for further studies on the regulation of mRNA expression.…”
mentioning
confidence: 98%